Mighty inside - Frazier, Sundee Tucker, 1968- (Levine Querido, 2021)
Freshman Melvin Robinson is one of only two Black students in his 1950s Spokane, Washington high school. He also has a stutter which has worsened since a bully targeted him. His new friend Lenny, a Jewish jazz saxophonist who lives above a segregated club, encourages Melvin to talk to his crush Millie and join him in trying out for a local television variety show. As Melvin's confidence grows, he learns to use his voice to speak up when it matters most, and to be as mighty on the outside as he is on the inside.